Anti-amoebic effects of synthetic acridine-9(10H)-one against brain-eating amoebae - Usman, Ahmed *; Manzoor, Mehwish; Qureshi, Sehrish; Mazhar, Muzna; Fatima, Arj; Aurangzeb, Sana; Hamid, Mehwish; Khan, Khalid Mohammed; Khan, Naveed Ahmed; Rashid, Yasmeen; Ayaz, Anwar * (Elsevier, 2023)
Pathogenic A. castellanii and N. fowleri are opportunistic free-living amoebae. Acanthamoeba spp. are the causative agents of granulomatous amebic encephalitis (GAE) and amebic keratitis (AK), whereas Naegleria fowleri causes a very rare but severe brain infection called primary amebic meningoencephalitis (PAM). Acridinone is an important heterocyclic scaffold and both synthetic and naturally occurring derivatives have shown various valuable biological properties. In the present study, ten synthetic Acridinone derivatives (I-X) were synthesized and assessed against both amoebae for anti-amoebic and cysticidal activities in vitro. In addition, excystation, encystation, cytotoxicity, host cell pathogenicity was also performed in-vitro. Furthermore, molecular docking studies of these compounds with three cathepsin B paralogous enzymes of N. fowleri were performed in order to predict the possible docking mode with pathogen. Compound VII showed potent anti-amoebic activity against A. castellanii with IC50 53.46 µg/mL, while compound IX showed strong activity against N. fowleri in vitro with IC50 72.41 µg/mL. Compounds II and VII showed a significant inhibition of phenotypic alteration of A. castellanii, while compound VIII significantly inhibited N. fowleri cysts. Cytotoxicity assessment showed that these compounds caused minimum damage to human keratinocyte cells (HaCaT cells) at 100 µg/mL, while also effectively reduced the cytopathogenicity of Acanthamoeba to HaCaT cells. Moreover, Cathepsin B protease was investigated in-silico as a new molecular therapeutic target for these compounds. All compounds showed potential interactions with the catalytic residues. These results showed that acridine-9(10H)-one derivatives, in particular compounds II, VII, VIII and IX hold promise in the development of therapeutic agents against these free-living amoebae.